2012
DOI: 10.1016/j.neuropsychologia.2012.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in default and reward networks during processing of personally relevant information

Abstract: We recently found activity in default mode and reward-related regions during self-relevant tasks in young adults. Here we examine the effect of aging on engagement of the default network (DN) and reward network (RN) during these tasks. Previous studies have shown reduced engagement of the DN and reward areas in older adults, but the influence of age on these circuits during selfrelevant tasks has not been examined. The tasks involved judging personality traits about one's self or a well known other person. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 125 publications
2
18
0
1
Order By: Relevance
“…Numerous prior studies have shown reduced connectivity within the default network during rest (Andrews-Hanna et al, 2007; Damoiseaux et al, 2008; Grady, Grigg, & Ng, 2012; Hampson et al, 2012; Meier et al, 2012; Mevel et al, 2013; Onoda, Ishihara, & Yamaguchi, 2012; Sala-Llonch et al, 2012; Saverino, Grigg, Churchill, & Grady, 2015). As reviewed above, studies also report altered connectivity between default and other brain networks (Betzel et al, 2014; Chan et al, 2014; Geerligs et al, 2015; Keller et al, 2015; Meunier et al, 2009; Wu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous prior studies have shown reduced connectivity within the default network during rest (Andrews-Hanna et al, 2007; Damoiseaux et al, 2008; Grady, Grigg, & Ng, 2012; Hampson et al, 2012; Meier et al, 2012; Mevel et al, 2013; Onoda, Ishihara, & Yamaguchi, 2012; Sala-Llonch et al, 2012; Saverino, Grigg, Churchill, & Grady, 2015). As reviewed above, studies also report altered connectivity between default and other brain networks (Betzel et al, 2014; Chan et al, 2014; Geerligs et al, 2015; Keller et al, 2015; Meunier et al, 2009; Wu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the coherent pattern of activation observed in these regions during a resting state, researchers termed this set of regions the “default mode network” (84). Studies have consistently shown that with advanced age, coordinated activity between the areas of the default mode network decreases, suggesting a disruption of the endogenously evoked brain signal with aging (80, 82, 83). Furthermore, studies have shown that under cognitive challenge, older adults have more difficulty switching out of the default state, resulting in default mode activity that is more active and less suppressed during a task in older adults compared to younger adults (81, 87).…”
Section: The Impact Of Obesity On Cognition Across the Adult Lifespanmentioning
confidence: 99%
“…Age differences in functional connectivity have been examined extensively for the default network (e.g., Andrews-Hanna et al, 2007;Damoiseaux et al, 2008;Grady et al, 2012), and to some extent for other brain networks (Allen et al, 2011;Campbell et al, 2012;Onoda et al, 2012;Rieckmann et al, 2011;Thomas et al, 2013;Tomasi and Volkow, 2012;Voss et al, 2010). Weaker functional connectivity has been reported specifically within the SLN or in SLN nodes in older adults (Allen et al, 2011;Geerligs et al, in press;He et al, 2014;Meier et al, 2012;Onoda et al, 2012;Tomasi and Volkow, 2012), leading us to predict age-related reductions in SLN functional connectivity in our results, although connectivity within the striatum, a node of the SLN, has been shown to increase with age (Allen et al, 2011;Tomasi and Volkow, 2012;Wang et al, 2012).…”
Section: The Current Studymentioning
confidence: 99%